Evaluation of extruded roughage with different additives in sheep diet - Tamires Soares de Assis; Erica Beatriz Schultz; Karla Alves Oliveira; Marco Túlio Santos Siqueira; Luciano Fernandes Sousa; Gilberto de Lima Macedo Junior (Acta Scientiarum. Animal Sciences, 2021)
The purpose was to evaluate the effect of extruded roughage Foragge® with different additives on intake, digestibility nutrients and nitrogen balance of sheep. Twenty adults, non-pregnant ewes with average weight 68 kg were used. The treatments were extruded roughage with additives (essential oil, virginiamycin, unpurified inactive yeast, tannin and purified inactive yeast). The design was in randomized blocks. The means were contrasted by SNK test, and the fecal score was tested by the Kruskal Wallis test (1952), at 5% significance. There was no difference in the intake of dry matter, crude protein, nitrogen, water, water in relation to dry matter, neutral detergent fiber (NDF), and acid detergent fiber (p > 0.05). As well as the digestibility of dry matter, crude protein and neutral detergent fiber, the fecal weight, fecal nitrogen, retained nitrogen and nitrogen retained in relation to nitrogen ingested (p > 0.05). However, dry matter intake as a function of body weight and metabolic weight, urinary nitrogen, hemicellulose intake, and hemicellulose as a function of NDF, were higher in the Foragge Factor® treatment (p < 0.05). The inclusion of different additives in the extruded roughage improved nutritional parameters, without causing disturbances.